"Selling" Europe on free enterprise: Advertising, business and the US State Department in the late 1940s. (15th February 2016) - Stole, Inger L.
Abstract : Purpose: – A number of scholars have explored the US Government's postwar efforts, often in collaboration with the business community, to "sell America" to Americans themselves; others have documented the means through which such information was aimed at audiences behind the Iron Curtain. Few scholars have explored the use of the US "propaganda" to secure political loyalty and financial markets among Western allies, and fewer still have studied the government's use of commercial marketing methods for this purpose. Attempting to fill a void, this paper aims to explore the US State Department's postwar collaboration with the Advertising Council, a non-profit organization funded and organized by American business, to "sell" the 16 countries that were receiving aid under the Marshall Plan on "the American way of life". Design/methodology/approach: – Drawing primarily from archival sources, the underlying research here is heavily based on various State Department collections housed at the National Archives in Washington, DC, and College Park, Maryland, as well as documents from the Harry S. Truman Library in Independence, Missouri, and the Advertising Council Archives at the University of Illinois. Findings: – In contrast to its many successes during the Second World War, the Advertising Council's first international project was plagued by erroneous assumptions and unforeseen problems, making the "Overseas Information" campaign far less successful than its previous projects. Thus, the case study holds lessons for the US Government in any future attempts to use the assistance of commercial advertisers in attaining its "soft power" objectives. Research limitations/implications: – The study explores the "Overseas Information" campaign from an institutional perspective only. Future research should focus on public perceptions of the campaign and possibly a rhetorical analysis of the actual advertisements. Practical implications: – The case study holds lessons for the US Government in any future attempts to use the assistance of commercial advertisers in attaining its "soft power" objectives. Social implications: – The study reveals interesting, and heretofore, unrevealed information about collaborations between the government and US business in the postwar era. Originality/value: – Up till this point, the Advertising Council's "Overseas Information" has received very scant scholarly attention and few, if any, have recognized its importance in the ongoing quest for government "soft power" in the postwar era.